2012
DOI: 10.1111/jnc.12007
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cholesterol in dopamine transporter function

Abstract: The conformation and function of the dopamine transporter (DAT) can be affected by manipulating membrane cholesterol, yet there is no agreement as to the impact of cholesterol on the activity of lipid-raft localized DATs compared to non-raft DATs. Given the paucity of information regarding the impact of cholesterol on substrate efflux by the DAT, this study explores its influence on the kinetics of DAT-mediated DA efflux induced by dextroamphetamine, as measured by rotating disk electrode voltammetry (RDEV). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 76 publications
(232 reference statements)
7
103
0
Order By: Relevance
“…The role PKC plays in the interactions between DAT and flotillin-1/membrane rafts still remains unclear; however. Cremona et al (2011) also reported that flotillin-1 is required for AMPH-triggered, DAT-dependent DA efflux, a process others have reported to depend on DAT localization to cholesterol-rich raft domains (Jones et al, 2012). Together, these studies point to the existence of PKCdependent regulation of DAT protein associations as critical to the response of the transporter to display altered function and/or trafficking.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 72%
“…The role PKC plays in the interactions between DAT and flotillin-1/membrane rafts still remains unclear; however. Cremona et al (2011) also reported that flotillin-1 is required for AMPH-triggered, DAT-dependent DA efflux, a process others have reported to depend on DAT localization to cholesterol-rich raft domains (Jones et al, 2012). Together, these studies point to the existence of PKCdependent regulation of DAT protein associations as critical to the response of the transporter to display altered function and/or trafficking.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 72%
“…However, it is unclear whether antibody-bound DAT traffics similar to native DAT, as we investigate here. Multiple studies also demonstrate that DAT partitions into cholesterol-rich membrane microdomains (36,(39)(40)(41)(42)(43)(44) and that the membrane raft protein flotillin-1 is required for PKC-and AMPH-mediated DAT internalization (42), consistent with a clathrin-independent endocytic mechanism. However, a separate study reported that flotillin-1 contributes to DAT membrane mobility rather than PKC-stimulated DAT internalization (45).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, cholesterol depletion with MβCD significantly reduced the ability of DAT to take up dopamine without altering DAT surface expression in LLC-PK1, HEK293 and N2A cells [40,41,44]. Furthermore, cholesterol depletion with MβCD attenuates the ability of DAT to reverse transport dopamine in HEK293 and N2A cells [41,44]. Accordingly, knockdown of DAT-associated flottilin-1 proteins results in attenuation of amphetamine efflux in primary mesencephalic dopaminergic neurons, further demonstrating the importance of lipid raft localization in DAT function.…”
Section: Cholesterol Content and The Function Of Transporters/ Receptorsmentioning
confidence: 88%
“…For instance, exogenously increasing membrane cholesterol level in striatal synaptosomes and neuronal-like MN9D cells increases the binding B max values for cocaine analogs but had no effect of DAT surface level [51]. Moreover, cholesterol depletion with MβCD significantly reduced the ability of DAT to take up dopamine without altering DAT surface expression in LLC-PK1, HEK293 and N2A cells [40,41,44]. Furthermore, cholesterol depletion with MβCD attenuates the ability of DAT to reverse transport dopamine in HEK293 and N2A cells [41,44].…”
Section: Cholesterol Content and The Function Of Transporters/ Receptorsmentioning
confidence: 99%
See 1 more Smart Citation